Use of wound edge inversion (epibole) to generate recalcitrant and inflamed diabetic wounds. Issue 1 (2nd September 2022) - Lee, Phoebe L.; Loder, Shawn J.; Guerrero, David T.; Nerone, W. Vincent; Bengur, Fuat Baris; Rubin, J. Peter; Kokai, Lauren E.
Abstract: Robust and predictive pre‐clinical models of recalcitrant diabetic wounds are critical for advancing research efforts toward improving healing. Murine models have logistic and genetic benefits versus larger animals; however, native murine healing inadequately represents clinically recalcitrant wounds in humans. Furthermore, current humanization techniques employing devices, deleterious mutations or chemical agents each carry model‐specific limitations. To better replicate human wounds in a mouse, we developed a novel wound‐edge inversion (WEI) technique that mimics the architecture of epibole and mitigates contracture, epithelialization, and consequently wound closure. In this study, we evaluated the reliability and durability of the WEI model in wild‐type and obese diabetic mice and compared to healing after (i) punch biopsy, (ii) mechanical/silicone stenting or (iii) exogenous oxidative stressors. In wild‐type mice, WEI demonstrated favourable closure characteristics compared to both control and stented wounds, however, wounds progressed to closure by 4 weeks. In contrast, diabetic WEI wounds persisted for 6–10 weeks with reduced contracture and epithelialization. In both diabetic and wild‐type mice, WEI sites demonstrated persistence of inflammatory populations, absence of epithelialization, and histologic presence of alpha‐SMA positive granulation tissue when compared to controls. We conclude that the WEI technique is particularly valuable for modelling recalcitrant diabetic wounds with sustained inflammation and dysfunctional healing.